2020
DOI: 10.3389/fonc.2020.01508
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of LncRNA C1RL-AS1 Suppresses the Malignant Phenotype in Gastric Cancer Cells via the AKT/β-Catenin/c-Myc Pathway

Abstract: Purpose: Numerous studies have shown that lncRNAs play vital roles in the development and progression of cancer. However, investigations of lncRNAs in gastric cancer are limited and need to be further pursued. Materials and Methods: According to RNA-seq results of gastric cancer (GC) tissues, we identified a novel lncRNA, C1RL-AS1. qRT-PCR was used to detect the expression level of C1RL-AS1 in paired GC and normal tissues. Nuclear/cytoplasmic fractionation was applied to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…These results demonstrated that ITGB1-DT activated Wnt/β-catenin pathway in LUAD. MYC is a well-known Wnt/β-catenin downstream target and exhibits oncogenic roles in various cancers ( Zhen-Hua et al, 2020 ). Thus, we further detected the effects of ITGB1-DT on MYC expression.…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrated that ITGB1-DT activated Wnt/β-catenin pathway in LUAD. MYC is a well-known Wnt/β-catenin downstream target and exhibits oncogenic roles in various cancers ( Zhen-Hua et al, 2020 ). Thus, we further detected the effects of ITGB1-DT on MYC expression.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, prostate cancer-associated transcript 6 (PCAT6) could promote the oncogenesis and angiogenesis of triple-negative breast cancer by regulating VEGFR2 ( 35 ). AKT/β-catenin/c-Myc pathway was activated by C1RL-AS1 to promote the cancerous behavior in stomach adenocarcinoma cells ( 36 ). Moreover, by affecting the miR-194-5p/FOXA1 axis, MCM3AP-AS1 has been shown to increase hepatocellular cancer growth ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…miR-16-5p was reported to be sponged by SNHG16, which served as a ceRNA, and so induce the derepression of its target gene SMAD5 and result in potentiation of the TGF-β1/SMAD5 pathway to upregulate the expression of CD73 in Vδ1 T cells [27]. C1RL-AS1 probably promoted the malignant phenotype of gastric cancer via the AKT/β-catenin pathway by downregulating c-Myc [28].…”
Section: Discussionmentioning
confidence: 99%